Glycemic trajectories of fasting blood glucose on the pathological responses in breast cancer women with and without concomitant diabetes - Saba Javed; Umar Javed; Dzul Azri Mohamed Noor; Nur Hafzan Md Hanafiah; Tanveer Mustafa; Anees ur Rehman; Sabariah Noor Harun (PLoS ONE, 2026)
Background Most existing studies have predominantly examined the impact of single blood glucose measurements without considering how fluctuations over time may influence clinical outcomes. Moreover, no studies have yet explored the effect of blood glucose trajectories on pathological responses in breast cancer patients undergoing neo-adjuvant chemotherapy (NACT), highlighting a significant gap in the current literature. Purpose To determine the impact of dynamic changes in blood glucose during neo-adjuvant chemotherapy on the pathological responses in women with breast cancer, with and without concomitant diabetes. Method This prospective cohort study was conducted among women with locally advanced breast cancer receiving treatment at GINUM Hospital in Gujranwala, Pakistan. Data for the prospective phase were collected from 20 January 2023 to–13 May 2024. Clinical data were obtained using a structured data collection form. Diabetes status was confirmed at baseline using Glycated hemoglobin (HbA1c) and Fasting blood glucose (FBG) tests. Patients were classified into glycemic trajectories based on the values of their FBG values during the treatment period. Results Five blood glucose trajectories were identified from the start of breast cancer treatment to the post-treatment period: normal glycemic trajectory (23 patients, 4.1%), erratic glycemic trajectory (130 patients, 23.2%), consistently hyperglycemic trajectory (127 patients, 22.7%), controlled diabetes (130 patients, 23.2%), and uncontrolled diabetes (150 patients, 26.8%). All glycemic trajectory groups demonstrated a non-significant increase in the odds of achieving Pathological partial response (pPR). Similar to pPR, the various categories of blood glucose trajectories were associated with a non-significant increase in the odds of Pathological no response (pNR). Among nondiabetic patients the group I(normal) and group III (consistently hyperglycemic) trajectories showed no significant interaction with pathological responses, as indicated by repeated measures ANOVA. Conclusion Our findings indicated that fluctuations in FBG levels among individuals with diabetes were not associated with pathological responses to neo-adjuvant chemotherapy. This suggests that the rise in blood glucose levels in diabetic patients are more likely driven by their pre-existing metabolic dysfunction rather than their chemotherapy related pathological responses.